Cosmetic Medicine: Innovative Beauty Care as Popular Medicine in Days Gone By - Locher, Wolfgang G. (Facial Plastic Surgery, 2016)
Throughout the ages, people yearned for beauty and longevity. This article examines how European physicians began to engage with the field of cosmetics over a century ago, thus introducing the category of aesthetics into medical practice. This historical phenomenon is currently repeating itself.
Keywords: cosmetic medicine; beauty; history; nonsurgical rejuvenation